Oxidation of 3-Hydroxyflavanones using Polymer-Supported [Hydroxy(tosyloxy)iodo]benzene - KUMAR, DEVINDER; KUMAR, SUNIL (Asian Journal of Chemistry, 2010)
The reaction of polymer-supported [hydroxy(tosyloxy)-iodo]benzene with 3-hydroxyflavanones has been described to afford 2,3-dimethoxy-3-hydroxyflavanones. This is a clean oxidation reaction with moderate to high yield.